Risk factors associated with pig pre-slaughtering losses - Dalla Costa, Osmar Antônio; Dalla Costa, Filipe Antonio [UNESP]; Feddern, Vivian; Lopes, Letícia dos Santos; Coldebella, Arlei; Gregory, Neville George; de Lima, Gustavo Julio Mello Monteiro (Elsevier, 2019)
The incidence of non-ambulatory non-injured (NANI), non-ambulatory injured (NAI)and dead pigs on-arrival at three Brazilian slaughterhouses were evaluated in 37,962 pigs to identify risk factors linked to them, besides carcass bruises and limb fractures. Total pre-slaughtering losses were 1.18%, in which NAI (0.39%)and NANI (0.37%)incidences contributed the most. A positive relation between on farm steeper ramp slope >20° and the incidence of NAI, NANI and dead pigs at unloading was found. Farm size, pigs/pen, enthalpy at loading, transportation time, truck loading order, muscle thickness and carcass weight, were identified as risk factors for pre-slaughtering losses. Loading procedures influenced the occurrence of limb fractures and bruises (which are a welfare issue and should be reduced). Therefore, personal training on pre-slaughter handling is essential to reduce the risk factors to improve animal welfare and avoid losses during the pre-slaughter process.
Keywords: Bruises; Carcass condemnation; Dead on-arrival; Fatigued pigs; Non-ambulatory pigs